Interpretasi Tanda Dalam Penokohan Cerpen “Syamsyūn Al- Jabbār” Karya Kāmil Kīlani (Kajian Semiotika Charles Sander Pierce) - Anasmilah Masitoh; Syaiful Islam (Uktub: Journal of Arabic Studies, 2023)
This study discusses the types of signs and their interpretation characterizations in the short story Syamsyūn Al-Jabbār by Kāmil Kilanī. The purpose of study is to interpret of signs in the characterization of the short story Syamsyūn Al-Jabbār. The theory used in this research is pierce semiotics which is know as triangle sign theory, that is representament, object, and interpretant. Pierce also divides the types of signs based on his object into three, that is icons, indexs, and symbols. The method used in this study is a descriptive qualitative method that examines the contents of the document. Based on the result of research on the Syamsyūn Al-Jabbār short stories, it was found first, there are three types of signs icon, indexs, and symbols used to find out the characters contained in the Syamsyūn Al-Jabbār stories. The Characters included six figures including Syamsyūn Al-Jabbār, Jamilah, Sultan, Dalilah, Pandai besi, and Menteri. Second, the interpretation of sign. Overall in the short story there are three aspects related to life, including aspect of strength, power, and beauty.